Pembentukan Political Branding Hendy Siswanto (Studi Kasus Pemilihan Bupati Jember Tahun 2020) - Sari, Agnes Aprillia; Erviantono, Tedi; Puspitasari, Ni Wayan Radita Novi (Jurnal Nawala Politika, 2023)
This study aims to determine the political marketing strategy used in the 2020 Jember Regency Regent Election campaign by one of the candidates for regent, Hendy Siswanto. In the process, campaign, a political marketing strategy is basically needed to build character and characteristics of the candidates. This study used a qualitative descriptive method through a literature review obtained from secondary data analysis. Based on the results of the analysis, it was found that the establishment of political branding by Hendy Siswanto focused on utilizing social media as a marketing medium. In addition, characteristics were also found based on three steps that must be carried out in political branding: brand identity (identity), brand image (image), and brand position (reputation). Keywords: Political Branding, Campaign, Election